Mechanisms and Emerging Therapies in Tremor Disorders - Grimaldi, Giuliana; Manto, Mario (Contemporary Clinical Neuroscience, 2013)
Tremor is intimately linked to the numerous interactions of the central and peripheral nervous system components tuning motor control, from the cerebral cortex up to the peripheral effectors. Activities of central generators, reflex loop delays, inertia, stiffness and damping are all factors influencing features of tremor. This book discusses the pathophysiology of tremor including membrane mechanisms and rodent models, the advances in genetics and the musculoskeletal models pertinent to body oscillations. The main forms of tremor encountered during clinical practice are considered, taking into account neuroimaging aspects. The book covers recent advances in methodologies and techniques of assessment, and provides practical informations for the daily management. In addition to pharmacological treatments, neurosurgical approaches such as deep brain stimulation (DBS) and thalamotomy are discussed. Emerging techniques under development are also introduced. Future challenges are also presented.